INFLUENCE OF REPEATED COMPACTION AND TRANSPORT LOADS ON THE CHARACTER OF HARDENING OF BELITIC SLUDGE IN LAYERS OF ROAD CLOTHES - A. A. Lytkin (Вестник СибАДИ, 2017)
The article describes the characteristic of belitic sludge - a large-tonnage waste of alumina production. The ability of the sludge to recover the destroyed structure after the re-compaction. The effect of multiple mobile loads on the nature of sludge hardening and sludge-crushed stone materials in a year-round cycle with a natural course of air temperature on the ring test bench. It is established that mobile loads have a positive effect on the hardening of these materials. After 20 months of operation, the strength of the sludge and sludge-crushed stone materials in the sections which is under the movement is 13.0% and 33.8% higher compared to the materials of the control sections. Therefore, there is no need to stop the traffic immediately after constructing the layers of pavements using slurry. Moreover, it should not regulate the time after which the slurry is allowed by the device base coating.